Reliability and Validity of Visual Estimation in Determining Thorax Rotation Mobility using the Quadruped Lumbar-Locked Position - Katelyn S Whetstone; Kyle A Matsel; Andrew S Patton; Sarah E Gehres; Kate Schwartzkopf-Phifer (International Journal of Sports Physical Therapy)
# Background